PENERAPAN MODEL PEMBELAJARAN COOPERATIVE-MEANINGFUL INSTRUCTIONAL DESIGN (C-MID) TERHADAP PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Komariah komariah; Abdul Rosyid; Zuli Nuraeni (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2017)
Application of Cooperative-Meaningful InstructionalDesign (C-MID) Learning Model to Improve Student Mathematical CommunicationSkill. This study aims to examine the improvement of students' mathematicalcommunication skills with Cooperative-Meaningful Instructional Design learningmodel. This research involves experimental class and control class which is takenfrom class VII (Seven) SMP Negeri 4 Kuningan academic year 2016/2017. Theinstruments used in this study are test and questionnaire. Through experimentalmethod of pretest result it is known that the average score of mathematicalcommunication ability of control class is 31,36 while experiment class is 27,15. Andresult of posttest known that average score of communication of control class is 37,17and mean score of mathematical communication of experiment class is 43,08. Fromthe calculation of N-Gain score, the average of experimental class is 0,45 and thecontrol class is 0,26, it shows that after being given treatment of improvement ofmathematical ability of experiment class communication better than improvement ofmathematical communication ability of control class. The improvement ofmathematical communication skills of the experimental class is in the mediumcategory. In addition, from the result of questionnaire of student response, it is knownthat the students showed a positive response to the C- Cooperative-MeaningfulInstructional Design (C-MID) learning model.